Analyzing Poses in Photocards as a Main Attraction to Collectors - Nabila Myisha; Dinda Sabila; Dinera Qurrotul Aini; Muizzu Nurhadi; Mirza Fathima Kamalia Jauhar (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
Analyzing the main attraction of photocards to collectors, in which the focus of this study is to analyze the poses of Enhypen’s photocards and on why certain poses might trigger the desire for collectors within this community to buy them. Photocards is one of the items included in the production of the album when idol groups are making their music comebacks. Photocard consists of a picture with an interesting pose and usually comes in a 5.5 x 8.5 cm photo and printed on a carton paper; some are as thick as a debit card, with designs ranging from a hologram to a lenticular. This study based the research of this topic using Barthes's semiotics theory and the theory of the circuit of culture by Stuart Hall as well as focusing on the consumption of the collectors using the theory of consumption by Baudrillard. Qualitative methods such as semiotics will be used to collect data while also used ethnographic design to interview collectors within the community on why they decided to collect photocards. The researchers has conducted interviews to answer the questions in this topic to seven collectors inside the community regarding the reason on whether or not they decided to collect photocards based on their poses or because of their expensive price.